Eksperimentasi Pembelajaran Matematika Dengan Metode Pembelajaran Problem Solving dan Probing Prompting Terhadap Hasil Belajar Matematika Ditinjau Dari Tingkat Berpikir Kritis Siswa - Primadani, Aisyah Ilmi, Sri Rejeki, M.Pd., M.Sc (2017)
The study aims at evaluating: (1) the difference effect of students' mathematics learning outcomes viewed from two different learning methods (Problem Solving and Probing Prompting), (2) the difference effect of tudents'mathematics learning outcomes viewed from different of critical thinking level of students, (3) the effect of interaction between the learning methods and critical thinking level of students on mathematics learning outcomes. This study is a quantitative research with quasi experiment research design. Theopulation of this study were all of grade VIII students of SMP Islam Al Abidin Surakarta, with sample experiment of grade VIII F and VIII E. The data collection was has conducted using test and documentation. The data was analyzed usingdifferent number of cell analysis of variance with a significance level of 5%. The conclusion are: (1) there is difference effects on students' mathematics learning outcomes viewed from two different learning methods, Problem Solving a give better result than Probing Prompting. (2) There is ifference effect on students' mathematics learning outcomes viewed from different of critical thinking level of students, students with high level of critical thinking better than students with low level of critical thinking. (3) There is no effect of interaction between learning methods and critical thinking level on mathematics learning outcomes.